2016
DOI: 10.1002/chem.201600259
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Proteome Profiling and Bioimaging Applications of Small‐Molecule Affinity‐Based Probes Derived From DOT1L Inhibitors

Abstract: DOT1L is the sole protein methyltransferase that methylates histone H3 on lysine 79 (H3K79), and is a promising drug target against cancers. Small-molecule inhibitors of DOT1L such as FED1 are potential anti-cancer agents and useful tools to investigate the biological roles of DOT1L in human diseases. FED1 showed excellent in vitro inhibitory activity against DOT1L, but its cellular effect was relatively poor. In this study, we designed and synthesized photo-reactive and "clickable" affinity-based probes (AfBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Despite previous reports of various chemical proteomic probes derived from SAH- and MT inhibitors, 26-30 the utility of such probes for broadly profiling human MTs in complex biological systems has remained unclear. Probes 5 and 6 , for instance, have been evaluated mainly in bacterial and plant systems, where they were found to enrich a handful of MTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous reports of various chemical proteomic probes derived from SAH- and MT inhibitors, 26-30 the utility of such probes for broadly profiling human MTs in complex biological systems has remained unclear. Probes 5 and 6 , for instance, have been evaluated mainly in bacterial and plant systems, where they were found to enrich a handful of MTs.…”
Section: Discussionmentioning
confidence: 99%
“…22-24 Similar strategies have begun to emerge for MTs, where, for instance, SAM analogues that transfer an alkyne have been used to identify MT substrates. 25 Likewise, first-generation photoreactive- and fluorescent/biotin-coupled probes based on the general MT inhibitors DzNep 26 and SAH, 27,28 as well as more selective DNMT 29 and DOT1L 30 inhibitors, have been introduced with the potential to enrich and identify MTs from native proteomes. While these previous efforts have succeeded in labeling and enriching a handful of MTs, the broader potential for chemical proteomic methods to target endogenous human MTs in complex biological systems with good scope and selectivity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in situ proteome labeling and PD : Labeling of recombinantly purified proteins (Bcl‐2 and Mcl‐1) with different probes was carried out similarly to in vitro proteome labeling experiments, based largely on previously published procedures with some modifications. For labeling of recombinant Mcl‐1 and Bcl‐2, different probes (5 μ m ) were added to a mixture of Mcl‐1 (1 μ m ), Bcl‐2 (1 μ m ), and BSA (1 μ m ) in PBS buffer (50 μL), and the reaction mixture was incubated for 2 h at room temperature with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy has recently become a powerful tool for large‐scale identification of potential “on” and “off” cellular targets of drug candidates. However, noncovalently interacting bioactive compounds account for >95 % of all FDA‐approved drugs and candidates . Thus, photoreactive groups (PGs), such as aryl azides, diazirines, and benzophenones, were further employed in ABPP probes to label interacting proteins covalently .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Furthermore,thanks to their broad spectrum of selectivity,ABPP probes have been used to screen prospective inhibitors against awide panel of proteins and show target engagement in the cellular environment. [3,4] Despite its widespread application to several different enzymatic families including kinases, [5] serine hydrolases, [6] and cysteine/threonine proteases, [7] only minor progress has been made with reference to epigenetic proteins.The value of developing activity-based probes directed against epigenetic modulators finds its rationale in the emerging potential of epigenetic proteins as therapeutic targets, [8] and it has been emphasized by recently reported successful attempts to use similar strategies in order to profile lysine methyl transferases, [9][10][11] or histone deacetylases. [12,13] However,asignificant amount of the afore mentioned studies rely on photo-affinity labelling techniques for the development of efficient probes,mostly because of the lack of activated or easily targetable nucleophilic amino acid residues in the active sites of these proteins.While there are no reports of effective ABPP probes against native bromodomains (BRDs), Daguer et al recently reported on the discovery of small molecules that are able to engage with ac onserved cysteine residue in the binding pocket when incubated with truncated bromodomains.…”
mentioning
confidence: 99%